Effects of Genetic Variation in Protease Activated Receptor 4 after an Acute Coronary Syndrome: Analysis from the TRACER trial - Tricoci, Pierluigi (Blood Cells Mol Dis, 2018)
Variation in platelet response to thrombin may affect the safety and efficacy of PAR antagonism. The Thr120 variant of the common single nucleotide polymorphism (SNP) rs773902 in the protease-activated receptor (PAR) 4 gene is associated with higher platelet aggregation compared to the Ala120 variant. We investigated the relationship between the rs773902 SNP with major bleeding and ischemic events, safety, and efficacy of PAR1 inhibition in 6177 NSTE ACS patients in the TRACER trial. There was a lower rate of GUSTO moderate/severe bleeding in patients with the Thr120 variant. The difference was driven by a lower rate in the smaller homozygous group (recessive model, HR 0.13 [0.02–0.92] p=0.042). No significant differences were observed in the ischemic outcomes. The excess in bleeding observed with PAR1 inhibition was attenuated in patients with the Thr120 variant, but the interactions were not statistically significant. In summary, lower major bleeding rates were observed in the overall TRACER cohort with the hyperreactive PAR4 Thr120 variant. The increase in bleeding with vorapaxar was attenuated with the Thr120 variant, but we could not demonstrate an interaction with PAR1 inhibition. These findings warrant further exploration, including those of African ancestry where the A allele (Thr120) frequency is ~65%.